1986
DOI: 10.1055/s-2007-1012430
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Retinopathy and its Association with Limited Joint Mobility

Abstract: Limited joint mobility (LJM) of the small joints of the hands was studied in 63 adult insulin-dependent diabetics to determine whether LJM might serve as an indicator to the presence of diabetic retinopathy in diabetics of long duration. In 123 non-diabetic controls, and in the 63 diabetics, the prevalence of LJM increased with age. In the diabetics, LJM was not associated with retinopathy, long-term glycaemic control or HLA type. The hypothesis that LJM is useful as a predictor of the development of retinopat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
4
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 8 publications
4
4
0
Order By: Relevance
“…34 Some reports demonstrated a link between long-term hyperglycemia and various diabetic hand changes, 13,19 while other reports failed to demonstrate such associations. 4,24,35,36 In our report, HgA1c was not found to be linked to any of the hand disorders, similar to other reports. 2,6,18,23 This is conceivable since a single or a mean HgA1c over a short period of time does not reflect long-term glycemic control.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…34 Some reports demonstrated a link between long-term hyperglycemia and various diabetic hand changes, 13,19 while other reports failed to demonstrate such associations. 4,24,35,36 In our report, HgA1c was not found to be linked to any of the hand disorders, similar to other reports. 2,6,18,23 This is conceivable since a single or a mean HgA1c over a short period of time does not reflect long-term glycemic control.…”
Section: Discussionsupporting
confidence: 92%
“…Tight glycemic control is linked to reduced microvascular complications in DM . Some reports demonstrated a link between long‐term hyperglycemia and various diabetic hand changes, while other reports failed to demonstrate such associations . In our report, HgA1c was not found to be linked to any of the hand disorders, similar to other reports .…”
Section: Discussionsupporting
confidence: 87%
“…The association of limited joint mobility with demographic variables was informative. This study confirms previous reports that limited joint mobility is associated with age (16,18,22,26,32). Although this was a cross-sectional study, there is little reason to suspect that the difference in mobility seen across patients of different age groups is related to anything but the aging process, especially since the general pattern is seen in both diabetic and control subjects.…”
Section: Discussionsupporting
confidence: 89%
“…Limitation of motion may also occur secondary to microangiopathy or neuropathy (13). The reported prevalence of limited joint mobility ranges from 11% to 55% in patients with insulin-dependent diabetes mellitus (IDDM) (3-5, [14][15][16][17][18][19][20][21][22][23][24], from 30% to 70% in patients with non-insulindependent diabetes mellitus (18,21,23-25), and from 1% to 20% in nondiabetic subjects (3,17,19,21,23,24). These wide ranges in reported prevalence are due to differences among the studies in terms of population selection, assessment methodology, and definition of limited joint mobility.…”
mentioning
confidence: 99%
“…However, the metabolic control did not correlate with the hand abnormalities. This perhaps somewhat unexpected finding is also reported by other authors [16,171 and also observed in patients with retinopathy [13, 181 but not in patients with nephropathy [15, 171. Our result might have been different if the metabolic control over a longer period of time had been investigated.…”
Section: Discussionsupporting
confidence: 79%